Pemodelan Value Layanan Informasi Industri dan Perdagangan dengan Metode TOGAF - Indri Koesnadi (Ikatan Ahli Informatika Indonesia, 2018)
Public value was a goal to be achieved by public service providers. Currently, public satisfaction with public service providers is still very limited. The scope of information services mostly focus on information dissemination.Value, ideally becomes the basis for modeling a public information service. That was influenced by community character and technical character. The public value approach was useful for increased trust and satisfaction with the delivery of public services. Department of Industry and Trade of West Java Province which has been the organizer of industry and trade affairs at Provincial level become the case study in Value Modeling of Information Service of Industry and Trade with TOGAF Method. The modeling was present in operational governance, operational technical services, process modeling and data modeling to improving the building block and metamodel formulation. That was an effort to improve the quality of information services. Through the modeling was expected to produce transparent information and open the space of collaboration with public participation so as to create the achievement of the public value that has been set in the planning documents.